Konsep Cinta Sebagai Upaya Harmonisasi dalam Konflik Antar Agama-agama Besar Dunia - Yoshy Hendra Hardiyan Syah; Rinni Winarti (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2022)
This article discusses the concept of love as a rare harmonization in conflicts between major world religions. The emergence of conflict is sometimes indicated by a certain ideology, power, and social-religious. The purpose of this research is to understand, respond to, and provide solutions to any conflicts that have occurred in the world’s major religions. In this study, using a qualitative research method with a descriptive analysis style using literature review techniques and using a historical review approach to explain descriptive analysis in discussing conflicts between the world’s major religions. What’s interesting about this article is that it offers the concept of love as taught in every religion. If without being based on love in realizing peace, it will be difficult to meet in deliberations, and greet one another. By taking the path of love, humans can create a harmonious life, a peaceful life without any disputes between other religious communities. So that with the diversity of people’s colors, religions, races, ethnicities, and cultures, we should be able to react wisely. Tolerance and mutual respect between fellow citizens must be upheld.